2018
DOI: 10.1111/1745-5871.12310
|View full text |Cite
|
Sign up to set email alerts
|

Discretion and the erosion of community trust in planning: reflections on the post‐political

Abstract: In this study, performance‐based planning is implicated in the destabilisation of community trust in the planning system. Set in a contested inner city area of Brisbane, Australia, the research associates neoliberal planning objectives with the discretionary decision‐making specifically embedded in performance‐based planning. The neoliberalisation of planning is, we submit, symptomatic of a post‐ideological politics of consensus that actually erodes properly political moments and renders the political merely a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…In terms of economic value, the identified theme seems to add another perspective in city branding literature. In comparison, Kwok et al (2018) see the economic value and city branding as equal priorities in some cities. Goess et al (2016) and Tataroğlu et al (2015) argue that city branding increases added economic value.…”
Section: Historic and Renowned Commoditymentioning
confidence: 99%
“…In terms of economic value, the identified theme seems to add another perspective in city branding literature. In comparison, Kwok et al (2018) see the economic value and city branding as equal priorities in some cities. Goess et al (2016) and Tataroğlu et al (2015) argue that city branding increases added economic value.…”
Section: Historic and Renowned Commoditymentioning
confidence: 99%
“…Local opponents of a development proposal may in fact articulate motives and concerns-for example, environmental protection-that "transcend their own narrow selfinterest" (Gibson, 2005:387). In neoliberal planning contexts, where public scrutiny is absent, planning decisions have been known to systematically favor developers (Kwok et al 2018). In authoritarian contexts, a lack of public participation has enabled governments to impose inappropriate planning decisions on communities that have no recourse (Pojani 2017).…”
Section: Theoretical Background On Nimbyismmentioning
confidence: 99%
“…However, YIMBY Action (2017) points out that DR "is a costly process whereby frivolous objections can slow down affordable housing for months or years." Academic research has found that discretion lowers public trust in the planning process and leads to discord (Kwok et al 2018). The YIMBY advocate quoted above states at a meeting:…”
Section: Nimbyism On Display During Public Meetingsmentioning
confidence: 99%
“…Moreover, existing residents worry that medium-density infill will introduce 'undesirable' people into traditional family orientated suburbs, in turn leading to increased social problems and falling property values (Burke 1991). Finally, many communities are increasingly distrustful of a neoliberal planning system that they see as a tool of property developers (Kwok, Johnson, and Pojani 2018).…”
Section: Community Barriersmentioning
confidence: 99%